Determining the Exposure of Benzene, Toluene, Xylene (in Condensate ) in a Chemical Laboratory of Natural Gas Company by Chemical Health Risk Assessment (CHRA) - Nora Putri Sabilla1 , Noeroel Widajati2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Chemical risk assessment is needed to find out how high the hazard level of chemicals in thelaboratory. This chemical health risk assessment will assess how often the chemical is exposed to workers,how much exposure it is so that the level of risk can be understood. The purpose of enabling decisions to bemade on appropriate control measure, training of employees, monitoring and surveillance activities as maybe required to protect the health of employees who may exposed by hazardous chemicals to health at work.Methods: This research is research with a qualitative approach. Based on the data collected, this study isobservational. This study uses the Chemical Health Risk Assessment (CHRA) method. This method is carriedout by identifying chemicals, determining Hazard Rating, evaluating exposure, assessing the adequacy ofthe control measures that have been carried out, concluding the CHRA results, and identifying the effortsthat need to be made.Result: In this study, there are three work units, namely a wet laboratory, oil laboratory, and gas laboratory.The chemicals analyzed are benzene, toluene, and xylene in the condensate. The hazardous chemical havesignificant risk now and already adequately controlled could increase in future (C2) which mean that theemployees are at risk due to hazardous chemicals and it adequately controlled but the risk can increase inthe future.Conclusion : Therefore, several steps can be taken to control the risk of health hazards from benzene,toluene, and xylene in the condensate, for example: determine precaution to maintain controls and minimizechances of higher exposure occurring; determine additional measures for regaining control if a high-riskevent occurs despite precaution; identify measures, procedures, and equipment to prevent or control anyaccidental emission of chemical hazardous to health, determine if monitoring or health surveillance isrequired to check on the effectiveness of controls; and review assessment every five years or when is achange in circumstances